Indicadores financeiros e operacionais mais relevantes para a avaliação de desempenho de empresas não-financeiras listadas na B3 - Neto, Miguel Tavares Ferreira (Universidade Federal de São Carlos, 2021)
This research seeks to analyze which financial and operational indicators most impact the performance of non-financial companies listed on the B3. The study is exploratory and was used a statistical method called factor analysis, capable of establishing from quantitative analyses the relationships and behaviors of the data studies. The indicators selected for the study were: gross margin, net margin, return on equity, return on assets, total assets, current liquidity, general liquidity, degree of indebtedness, total indebtedness, EBITDA margin, EBIT margin and asset turnover. With the results expressed, it was perceived that profitability indicators are the largest responsible for financial performance (48% of the variance recorded), followed by liquidity indicators (23%). Regarding the operational perspective, it was not possible to construct a forceful analysis, because the results obtained by the selected indicators were invalidated in the model.
Most relevant financial and operational indicators for evaluating the performance of non-financial companies classified in B3
Keywords: Indicadores financeiros; indicadores operacionais; desempenho; Análise fatorial; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA